Market Operations are Carried Out by the Trade Service As an Effort to Overcome Inflation and Stability of Staple Food Prices in the Balikpapan City Community - Muharramah, Zakiyyatu; Anwar, Khairil; Permanasari, Devi; Totalia, Sherly Sustantien (Unram Journal of Community Service, 2024)
This study analyzes the role of Market Operations carried out by the Balikpapan City Trade Office in an effort to maintain the stability of staple food prices and reduce the impact of inflation. Using a qualitative approach through interviews and observations, this study was conducted to evaluate whether the activity was effective in stabilizing staple food prices and increasing people's purchasing power. This study shows that Market Operations make a significant contribution to the provision of staple food at affordable prices, as well as increasing access for lower-middle class groups. This study suggests the need to increase the frequency and reach of market operations as part of regional economic policies in order to achieve better food security in Balikpapan City.